Labelling, certification and branding of cheeses in the southeastern Alps (Italy, Slovenia): Montasio, Bovec, Tolminc and Mohant cheese: - Ledinek Lozej, Špela (Acta geographica Slovenica, 2021)
The paper presents various collective instruments used in the labelling, certification and branding of cheeses in the southeastern Alps of Slovenia and Italy. Based on long term ethnography it discusses four case studies of Montasio, Bovec, Tolminc, and Mohant cheeses, that were awarded protected designation of origin at European Union level. The impact of geographical indications on the local dairy chains is compared to other instruments, ranging from top-down European and national quality schemes and inventories of traditional agricultural products and heritage, to grass-root initiatives such as Slow Food instruments and local brands. The study finds substantial difference in the use and impact of geographical indications in Italy and Slovenia, as well as several ambiguous and dissonant effects in all the identified instruments.